There are different shades of green: Heterogeneous environmental innovations and their effects on firm performance - Gianluca Biggi; Andrea Mina; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
Using a firm-level dataset from the Spanish Technological Innovation Panel (2003-2016), this study explores the characteristics of environmentally innovative firms and quantifies the effects of pursuing different types of environmental innovation strategies (resource-saving, pollution-reducing, and regulation-driven innovations) on sales, employment, and productivity dynamics. The results indicate, first, that environmental innovations tend to be highly correlated with firms' technological capabilities, although to varying degrees across types of environmental innovation, whereas structural characteristics are less significant. Second, we observe heterogeneous effects of different types of environmental innovation on performance outcomes. We find no evidence that any type of environmental innovation fosters sales growth while pollution-reducing and regulation-driven innovations boost employment growth. Moreover, both resource-saving and pollution-reducing innovations bring about productivity advantage.
Keywords: 330; Environmental Innovation; Green Investments; Resource-saving; Pollution-reduction; Environmental compliance; Firm performance